2023
DOI: 10.1111/epi.17482
|View full text |Cite
|
Sign up to set email alerts
|

Spike patterns surrounding sleep and seizures localize the seizure‐onset zone in focal epilepsy

Abstract: Objective: Interictal spikes help localize seizure generators as part of surgical planning for drug-resistant epilepsy. However, there are often multiple spike populations whose frequencies change over time, influenced by brain state.Understanding state changes in spike rates will improve our ability to use spikes for surgical planning. Our goal was to determine the effect of sleep and seizures on interictal spikes, and to use sleep and seizure-related changes in spikes to localize the seizure-onset zone (SOZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Interictal activity is consistently recorded in most patients with epilepsy and experimental models. Interictal activity is also brain state‐dependent, with a higher occurrence rate during NREM than in REM or wake 10 . Although interictal activity is regulated in a circadian pattern in a patient‐specific manner, 3,4 a high spike rate does not necessarily correlate with an increased seizure probability during the night and day cycle; they can even be in anti‐phase 3,4 .…”
Section: Sleep Wake and Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Interictal activity is consistently recorded in most patients with epilepsy and experimental models. Interictal activity is also brain state‐dependent, with a higher occurrence rate during NREM than in REM or wake 10 . Although interictal activity is regulated in a circadian pattern in a patient‐specific manner, 3,4 a high spike rate does not necessarily correlate with an increased seizure probability during the night and day cycle; they can even be in anti‐phase 3,4 .…”
Section: Sleep Wake and Seizuresmentioning
confidence: 99%
“…Interictal activity is also brain state-dependent, with a higher occurrence rate during NREM than in REM or wake. 10 Although interictal activity is regulated in a circadian pattern in a patient-specific manner, 3,4 a high spike rate does not necessarily correlate with an increased seizure probability during the night and day cycle; they can even be in anti-phase. 3,4 Similar findings in terms of circadian regulation of interictal activity have been found in rodent models of epilepsy.…”
mentioning
confidence: 99%
“…44,45 In line with these investigations, Conrad et al explored whether sleep and seizure-related changes in spikes allow for localization of the seizure-onset zone. 46 Bou Assi et al explored functional connectivity (in terms of phase-locking value) during interictal spikes and showed a decrease in global connectivity (in the gamma frequency band) time-locked to the spike peak. 47 Authors reported that functional connectivity was lower within the epileptic focus than outside the focus.…”
Section: Intracranial Eeg Recordingsmentioning
confidence: 99%
“…More recently, subpopulations of spikes were investigated based on features such as spike rate, line length, skewness of the spike distribution, and energy for the prediction of surgical outcomes 44,45 . In line with these investigations, Conrad et al explored whether sleep and seizure‐related changes in spikes allow for localization of the seizure‐onset zone 46 . Bou Assi et al explored functional connectivity (in terms of phase‐locking value) during interictal spikes and showed a decrease in global connectivity (in the gamma frequency band) time‐locked to the spike peak 47 .…”
Section: Recent Advances In Quantitative Eeg Analysismentioning
confidence: 99%
“…We additionally replicated this analysis with interictal epochs that were matched for state of wakefulness (see supplementary information). Briefly, bivariate features from each preictal epoch were normalized by those from ten interictal epochs with similar states of wakefulness (measured as alpha-delta ratio [40]) instead of 20 awake interictal epochs. At the group level, we refit a linear mixed effects model with the median absolute z scores and compared the outputs of the linear mixed effects models from the supplementary analysis (figure S7(A)) with the main text result (figure 4(A)).…”
Section: Deviations In Preictal Ieeg Network Node Strength From Basel...mentioning
confidence: 99%